METODE FIKIH, METODE SYARAH, TEKNIK PENDEKATAN, DAN TEKNIK INTERPRETASI DALAM MEMAHAMI HADIS - Awal Rifai Wahab; Ahmad Syaripudin (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2023)
This study aims to determine the fiqh method, syarah method, approaches, and interpretation techniques in understanding hadith. This research is library research using a qualitative descriptive approach. The results of the study show that in understanding hadith there are various ways and techniques of interpretation, one of which is understanding using textual and contextual methods. Likewise in the syarah of hadiths which can be carried out using several methods, including the taḥlīlī method, the ijmālī method, the muqāran method, and the mauḍū`ī method. While the approach that can be used in understanding the hadith is an interdisciplinary and multidisciplinary approach. As for hadith interpretation techniques, we can use linguistic, historical, scientific interpretation techniques, and so on. This research is expected to increase public interest in studying ʿulūm al-Ḥadiṡ, especially methods in explaining and understanding the hadith of the Prophet, so that efforts to revive sunnah can be achieved in the midst of Muslim society.